2021
DOI: 10.7759/cureus.18470
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Maculopathy and Outcomes After Treatment With Corticosteroids and Lutein

Abstract: This case report presents treatment outcomes for a patient with accidental laser-induced retinal injury. A 30-year-old man was evaluated for a sudden decrease of vision and metamorphopsia in his left eye after staring at a laser in a nightclub five days before presentation. Eye examination showed left visual acuity of 6/18-2 unaided, which improved to 6/12-2 on the pinhole test. Dilated fundoscopy showed a yellow-orange foveolar lesion in the left eye. Optic coherence tomography (OCT) showed an alteration of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In milder cases where surgeries are not indicated, evidence-based medical intervention is limited. Several studies showed visual and structural improvement with a short course of oral corticosteroid treatment immediately after the laser exposure 1,12–15 . The corticosteroid was suggested to reduce inflammatory response by decreasing the retinal pigment epithelium migration and proliferation in response to the laser-related injury 12,13 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In milder cases where surgeries are not indicated, evidence-based medical intervention is limited. Several studies showed visual and structural improvement with a short course of oral corticosteroid treatment immediately after the laser exposure 1,12–15 . The corticosteroid was suggested to reduce inflammatory response by decreasing the retinal pigment epithelium migration and proliferation in response to the laser-related injury 12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…5 In general, most of the reported laser retinal injury cases showed reversible retinal damage with corticosteroid or surgical treatment, although having a permanent scotoma was also not uncommon. 5,[11][12][13][14][15] Previous literature showed the management of laser retinal damage cases including observation, 9 oral corticosteroid, 1,[12][13][14][15] and surgical intervention, 11 depending on the injury severity.…”
Section: Management Of Laser Retinal Injurymentioning
confidence: 99%
See 3 more Smart Citations